2020
DOI: 10.1186/s13063-020-04785-2
|View full text |Cite
|
Sign up to set email alerts
|

Pulp repair response after the use of a dentin-pulp biostimulation membrane (BBio) in primary teeth: study protocol for a randomized clinical trial

Abstract: Background Vital pulp therapy aims at maintaining the pulp tissue injured but vital. Thus, the use of capping materials that induce tissue regeneration is a great current trend. This study aims to evaluate clinically and radiographically the pulp repair after the use of dentin-pulp biostimulation membrane in primary teeth. Methods Four hundred and sixty-eight teeth from children aged between 5 and 9 years old, both genders, with deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Therefore, to achieve a better success rate for the pulp capping, we considered it was essential to elucidate the pulpal wound-healing mechanism and to develop a novel material to promote this process. There have been reports of pulp-capping materials developed with the aim of achieving higher success rates while retaining the original biomaterial properties ( Nakashima et al 2003 ; Iohara et al 2004 ; Walker et al 2019 ; Machado et al 2020 ). However, no pulp-capping material with novel concepts based on the pulpal wound-healing process has been commercialized since the development of HCSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to achieve a better success rate for the pulp capping, we considered it was essential to elucidate the pulpal wound-healing mechanism and to develop a novel material to promote this process. There have been reports of pulp-capping materials developed with the aim of achieving higher success rates while retaining the original biomaterial properties ( Nakashima et al 2003 ; Iohara et al 2004 ; Walker et al 2019 ; Machado et al 2020 ). However, no pulp-capping material with novel concepts based on the pulpal wound-healing process has been commercialized since the development of HCSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the local regeneration of the dentine-pulp complex has been suggested/investigated using a local delivery system loaded with perfect combination of growth factors, e.g., fibroblast growth factors and bone morphogenetic proteins, with a scaffold for DPSCs [ 69 , 122 , 123 ]. Moreover, use of a biostimulation membrane in the dentine-pulp complex has shown success in the maintenance of dental pulp tissue as well as the physiological process of exfoliation in primary teeth [ 2 ]. It has been suggested that, with the application of local biodegradable/biocompatible carrier vehicles to transfer signalling/bioactive molecules to the capping site in VPT, induction of odontoblastic-like cell differentiation, formation of reparative dentine, and stimulation of fibrodentine may be anticipated, the phenomena which, in turn, could result in the reconstitution of normal tissue architecture in the dentine-pulp interface [ 124 ].…”
Section: Biomaterialsmentioning
confidence: 99%
“…Nowadays, vital pulp therapy (VPT) modalities are regarded as increasingly common ministrations and/or minimally invasive procedures [ 1 ] implemented to conserve/preserve the vitality of the dental pulp and maintain its function when the vital connective pulpal tissue has been compromised but not fully impaired by various stimuli [ 2 , 3 ]. Currently, VPT is considered an important alternative ultraconservative approach to conventional root canal therapy techniques, since it seems to (i) promote regenerative endodontics [ 4 ], (ii) preserve dental structure and function in the oral cavity [ 5 ], (iii) cause more tooth resistance against masticatory forces compared to traditionally endodontically treated teeth [ 6 ], and (iv) maintain the physiological process in the exfoliation of primary teeth [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carious lesions in permanent teeth are traditionally treated with total removal of the carious tissue ( Bjørndal et al, 2019 , Duncan et al, 2023 ); but minimally invasive dentistry has encouraged the use of techniques to preserve the dentin structure, avoid damage to the dentine-pulp complex and maintain pulp vitality ( Duncan et al, 2023 ). In response to conditions of pulp inflammation and in line with the minimally invasive proposal, vital pulp therapy (VPT) modalities are options that aim to preserve pulp vitality and maintain tooth functionality, through the correct management of pulp exposures and inflammation ( Machado et al, 2020 , Duncan et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%